2015
DOI: 10.18517/ijaseit.5.2.489
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repeated Heating on Fatty Acid Profile of Beef and Spices of Rendang

Abstract: Rendang is a traditional Minangkabau cuisine with the main ingredient of beef or buffalo meat which is cooked using coconut milk and some spices. Rendang is cooked more than 2 hours, and after that do the repeated heating. This study aimed to determine the effect of repeated heating on fatty acid profiles of beef and spices of rendang. The analysis carried out at Chemistry Lab. and Biochemistry Lab. In Fateta Unand and Integrated Lab in IPB Bogor. This study designed used a completely randomized design with 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Agar bumbu matang merata dan daging lebih empuk rendang harus selalu di aduk. Untuk memasak rendang daging ini dibutuhkan waktu selama 2 jam atau lebih bahkan sampai 5 jam (Yenrina et al, 2015). Scitech 2 (2):20-29 (2018) Proses memasak rendang yang butuh waktu lama ini cukup melelahkan dan menyita banyak waktu, maka dibutuhkan suatu alat bantu yang cukup praktis dan efisien untuk dapat membantu membuat rendang rumahan.…”
Section: Pendahuluanunclassified
“…Agar bumbu matang merata dan daging lebih empuk rendang harus selalu di aduk. Untuk memasak rendang daging ini dibutuhkan waktu selama 2 jam atau lebih bahkan sampai 5 jam (Yenrina et al, 2015). Scitech 2 (2):20-29 (2018) Proses memasak rendang yang butuh waktu lama ini cukup melelahkan dan menyita banyak waktu, maka dibutuhkan suatu alat bantu yang cukup praktis dan efisien untuk dapat membantu membuat rendang rumahan.…”
Section: Pendahuluanunclassified
“…It is also aimed at increasing the selling value/added value of livestock products. In Indonesia, rendang research generally revolves around evaluating the nutritional value of rendang, as reported by several studies including that of Murhadi (1994) regarding the heat resistance of bacteria in beef rendang, research by Yenrina et al (2015) regarding the effect of repeated heating of the fatty acid profile and research by Azima et al (2016) on the evaluation of the nutritional value of Minangkabau rendang. However, the amount of added value of rendang produced is not yet known, for that it is necessary to research how much added-value is produced through processing beef, chicken, eggs and lungs into rendang products that are processed by small industries in Payakumbuh City.…”
Section: Introductionmentioning
confidence: 99%